PEMETAAN PENELITIAN SEPUTAR COMPANY VALUE : ANALISIS BIBLIOMETRIK VOSVIEWER DAN LITERATUR REVIEW - Devi Oktaviani; Sri Andriani; Sulis Rochayatun (Accounting Journal of Ibrahimy (AJI), 2025)
This study used VOSviewer bibliometric analysis and literature review studies to map research and advances of scientific publications related to firm value. The research methodology combined qualitative approaches for literature review studies and quantitative methods for bibliometric analysis. It was then conducted by searching the Publish or Perish website for five years, from 2020 to 2025, using the keyword "Company Value." 492 research papers were found for this study. In order to visualize the evolution of subjects or study topics related to corporate value, the searched articles were first descriptively examined, then entered and examined using VOSviewer and literature studies. The findings demonstrated that the mapping visualization, which was done using VOSviewer, categorized the firm value research into 68 clusters and 4 items. In the meantime, there were five primary study themes regarding corporate value based on the findings of the literature review. The impact of firm value on sound corporate governance, firm size, capital structure, liquidity, and dividend policy were the most extensively studied study topics. Researchers might use the study's findings as a guide when they carried out additional research on company value.